Revisiting Textbook Adaption Through Open Educational Resources: An Inquiry into Students’ Emotions - Zhang, Xiaodong (International Review of Research in Open and Distributed Learning, 2020)
This qualitative study explored the emotional trajectories students experienced when faced with open educational resources (OER) that expanded the learning available from a required textbook. Data included students’ reflections, group discussions, and interviews, along with field notes which were collected in a classroom at a Chinese university in one semester. The study showed that students’ initial positive emotions arose from their understanding of their own learning needs. Their positive emotions toward the conjugated use of OER and a textbook fluctuated over the semester but were gradually enhanced through their involvement in classroom practices (e.g., knowledge building and teacher mediation). Through the process, students’ positive and negative emotions respectively facilitated and hampered their learning practices; however, negative emotions were not always detrimental—they also facilitated students’ learning. Students’ emotions gradually stabilized in the direction of being positive, especially in tandem with (a) achievement of sufficient knowledge gained through OER-based textbook use and teacher-mediated learning, and (b) their augmented confidence in proficiently using the new knowledge to navigate their practices.